The Effective Factors of Contemporary Dialogue (In the Light of Sheikh Ahmed Deedat's Dialouge) | أسباب فاعلية الحوار الدعوي المعاصر على ضوء حوار الشيخ أحمد ديدات - Ghilmanul Wasath (Al-Zahra : Journal for Islamic and Arabic Studies, 2009)
Muslim Scholars and du'at exerted exhaustive efforts for dialogue betweenIslam and other religions, not just for sharing ideas, understanding, andbuilding exclusive relations between religion’s followers, but for good result forIslamic propagation. The research deals with Sheikh Deedat’s long-experimentson debates and dialogues with Christians, Jews, and Hindus etc. His longexperiences proved that Islam far from being an extremist religion thatencourages violence, it is the religion of moderation, tolerance and mercy for allpeople and living beings. This study came to the essentiality of reasons fordialogue effectiveness in contemporary period. It emphasized the necessity ofinculcating islamic values and good habits for du'at as debater and dialogist. Italso emphasized the importance of planning and organizing, financing supportand communication multimedia for contemporary da’wah.